Pengembangan Lembar Kerja Siswa (LKS) Berbasis Model Discovery Learning Pada Tema 7 Kelas V SD Negeri 79 Lubuklinggau - Afiqoh Meynishfi; Tio Gusti Satria; Andri Valen (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This study aims to develop a learning product in the form of student worksheets (LKS) based on the Discovery Learning model on the theme of 7th grade V at SD Negeri 79 Lubuklinggau. This type of research is research and development (R & D) used Dick and Carrey model. The research sample or the subject of this study were 5th-grade students, totaling 9 students. data collection techniques were carried out through interviews and questionnaires. The data analysis technique uses the percentage value of the score obtained. The results showed that: 1) The quality of the LKS seen from the aspect of validity was included in the valid category with a percentage score of 83%; 2) The quality of the LKS seen from the practical aspect is categorized as practical, both individual student responses with a percentage score of 82% while for the percentage of small group student responses with a percentage score of 89% So it can be concluded that the LKS based on the Discovery Learning model on the theme of 7 events in life meets the valid and practical criteria so that it can be used in learning.